High‐Throughput Cell‐Free Screening of Eukaryotic Membrane Proteins in Lipidic Mimetics. Issue 8 (4th August 2022) - Bruni, Renato
Abstract: Membrane proteins (MPs) carry out important functions in the metabolism of cells, such as the detection of extracellular activities and the transport of small molecules across the plasma and organelle membranes. Expression of MPs for biochemical, biophysical, and structural analysis is in most cases achieved by overexpression of the desired target in an appropriate host, such as a bacterium. However, overexpression of MPs is usually toxic to the host cells and can lead to aggregation of target protein and to resistance to detergent extraction. An alternative to cell‐based MP expression is cell‐free (CF), or in vitro, expression. CF expression of MPs has several advantages over cell‐based methods, including lack of toxicity issues, no requirement for detergent extraction, and direct incorporation of target proteins in various lipidic mimetics. This article describes a high‐throughput method for the expression and purification of eukaryotic membrane proteins used in the author's lab. Basic Protocol 1 describes the selection and cloning of target genes into appropriate vectors for CF expression. Basic Protocol 2 describes the assembly of CF reactions for high‐throughput screening. Basic Protocol 3 outlines methods for purification and detection of target proteins. Support Protocols 1‐6 describe various accessory procedures: amplification of target, treatment of vectors to prepare them for ligation‐independent cloning, and the preparation of S30 extract, T7 RNA polymerase, liposomes, and nanodiscs. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Target selection, construct design, and cloning into pET‐based expression vectors Support Protocol 1 : Amplification of target DNA Support Protocol 2 : Preparation of ligation‐independent cloning (LIC)‐compatible vectors Basic Protocol 2 : Assembly of small‐scale cell‐free reactions for high‐throughput screening Support Protocol 3 : Preparation of Escherichia coli S30 extract Support Protocol 4 : Preparation of T7 RNA polymerase Support Protocol 5 : Preparation of liposomes Support Protocol 6 : Preparation of nanodiscs Basic Protocol 3 : Purification and detection of cell‐free reaction products